2009
DOI: 10.1159/000232488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Budesonide Inhalation on Energy Expenditure, Somatic Growth and Salivary Cortisol Levels in Preterm Infants with Chronic Lung Disease

Abstract: Background: We hypothesized that the use of inhaled budesonide (BUD) would alter somatic growth by increasing energy expenditure (EE) in premature infants with chronic lung disease (CLD). Methods: A prospective study was conducted of the effect of BUD on EE, growth and salivary cortisol excretion in infants with CLD who required supplemental oxygen and were treated with inhaled BUD for 4 weeks according the severity of their CLD, or without BUD treatment. Infants were compared with a healthy control group matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Saliva collection is easy to perform and reliable in adults and older children wherefore salivary concentrations of cortisol reflecting free cortisol concentrations in plasma is used to evaluate adrenal cortex function [4][5][6][7] . The best method of assessing adrenal function in preterm infants still is under debate but salivary cortisol measurement seems to be a promising diagnostic feature for these infants, too [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Saliva collection is easy to perform and reliable in adults and older children wherefore salivary concentrations of cortisol reflecting free cortisol concentrations in plasma is used to evaluate adrenal cortex function [4][5][6][7] . The best method of assessing adrenal function in preterm infants still is under debate but salivary cortisol measurement seems to be a promising diagnostic feature for these infants, too [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Many previously published studies conducted between 1990 and 2010 used the Deltatrac II indirect calorimeter. 11,18 To the best of our knowledge, this is the first study demonstrating longitudinal data of REE for healthy term infants at 1 and 2 months of age using a currently employed IC technology. ParvoMedics TrueOne 2400 IC provides highly accurate measurements of minute ventilation, VO 2 and VCO 2 as supported in previous publications by Crouter et al 22 and Cooper et al 23 Overall, we found a slight decrease in REE values from 1 to 2 months of age.…”
Section: Discussionmentioning
confidence: 91%
“…periods of time. [10][11][12][13] There are limited studies evaluating REE values immediately after birth [12][13][14][15][16] and sparse normative longitudinal REE data for healthy term infants at 1 and 2 months of age, which is a critical period of development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As of January 2011, 118 structures of TIM have been released in the PDB. The first apo structure of TIM from chicken muscle was deposited in 1976 (PDB entry 1tim; Banner et al, 1976). This was followed in 1990 by the deposition of the first ligand-bound structure of yeast TIM in the PDB [PDB entries 1ypi ) and 2ypi ].…”
Section: Introductionmentioning
confidence: 99%